Managing transition to ValueēBased hospital care pathways. (30th September 2020) - Scardoni, A; Sancini, S; Ambrosio, A; Signorelli, C; Odone, A
Abstract: Issue: San Raffaele Hospital (OSR) is part of a European alliance of 9 University Hospitals (EUHA) which promotes comparison and excellence in the clinical, research and training strategies. Description of the Problem: The development of Value-Based (VB) strategies has been active in OSR since March 2019, with multidisciplinary healthcare pathways and with the promotion of patient engagement. Results: The prostate cancer pathway was identified as a pilot and replicable model to promote the VB culture in different areas, in particular in the field of digitalization, human resources, research, redesigning of paths and outcomes collection. The other clinical pathways progressively launched during 2019 were: breast cancer, stroke, heart failure and pancreatic cancer. The project was realized by: setting up a Multidisciplinary disease teams; developing a training course on VB, involving all the healthcare professionals (clinicians and managers); involving patient associations in the development of the pathway; adopting sets of clinical outcomes, Patient-Related Outcome Measures (PROMs) and Patient-Related Experience Measures (PREMs) with a specific collection platform, currently under implementation; identifying new IT support tools, activated from March to December 2019 in 11 Disease Units: HealthMeeting, a platform supporting document and data sharing, connecting different Specialists and performing advanced digital multidisciplinary meetings; DNM-Digital Narrative Medicine, a platform connecting patients with their clinical team, supporting web-based storytelling and personalized therapeutic approach. Lessons: The introduction of a new shared and patient-centred work model, with the reorganization of spaces, resources and dedicated IT tools, has improved the diagnostic-therapeutic process. Key messages: The main challenge of hospital transition to VB pathways is organizational and cultural. For VB implementation is needed sustainable use of available resources and IT, to achieve better outcomes.